1977
DOI: 10.1002/pol.1977.170150505
|View full text |Cite
|
Sign up to set email alerts
|

Polymer radicals trapped in radical‐initiated polytetrafluoroethylene

Abstract: SynopsisThe electron spin resonance (ESR) spectra of polymer radicals found to be trapped in polytetrafluoroethylene (PTFE) polymerized with radical initiators were comparatively examined under various conditions and assigned. They are identified as the primary (propagating) radicals RCF~CFY, which are transformed to primary peroxy radicals RCF2CF200. in the atmosphere. Studies of the rates of polymerization and postpolymerization and ESR measurements indicate that the radical content steadily increases during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…4 In general, the addition of silica nanoparticles in a poly(VDF-co-HFP) matrix increases both corrosion resistance 5 and degradation temperature. [5][6][7] It also induces a reorganization of polymeric chains resulting in the decrease of crystallinity [8][9][10][11] and an increase of the mechanical properties. 12 However, interesting studies from Aravindan et al, 9 Ferrari et al, 11 and Saika and Kumar 7 reported that the best mechanical and thermal properties were obtained with an optimum amount of silica inserted into the nanocomposites composed of poly(VDF-co-HFP) copolymer comprised between 2.5 and 6 wt % and without nanoparticles aggregation.…”
mentioning
confidence: 99%
“…4 In general, the addition of silica nanoparticles in a poly(VDF-co-HFP) matrix increases both corrosion resistance 5 and degradation temperature. [5][6][7] It also induces a reorganization of polymeric chains resulting in the decrease of crystallinity [8][9][10][11] and an increase of the mechanical properties. 12 However, interesting studies from Aravindan et al, 9 Ferrari et al, 11 and Saika and Kumar 7 reported that the best mechanical and thermal properties were obtained with an optimum amount of silica inserted into the nanocomposites composed of poly(VDF-co-HFP) copolymer comprised between 2.5 and 6 wt % and without nanoparticles aggregation.…”
mentioning
confidence: 99%